The single‐chain anti‐TNF‐α antibody DLX105 induces clinical and biomarker responses upon local administration in patients with chronic plaque‐type psoriasis. Issue 6 (13th February 2016) - Tsianakas, Athanasios; Brunner, Patrick M.; Ghoreschi, Kamran; Berger, Claudia; Loser, Karin; Röcken, Martin; Stingl, Georg; Luger, Thomas; Jung, Thomas
Abstract: It is not clear whether TNF‐ α antagonists used in the treatment of psoriasis need to act systemically, or whether local inhibition of skin‐produced TNF‐ α would be sufficient to silence skin inflammation. To answer this question, we conducted two multicentre, double‐blinded, randomized, placebo‐controlled clinical trials with the novel single‐chain anti‐TNF‐ α ‐PENTRA ® ‐antibody DLX105. Upon intra‐dermal injection, DLX105 induced a mean local PASI decrease of 33% over baseline after 2 weeks of treatment, while the placebo response was only 12% ( P = 0.001). The clinical response was accompanied by changes in biomarkers such as reductions in K16, Ki67 and epidermal thickness as well as decreased mRNA levels of IL‐17, TNF‐ α, IL‐23p19, IL‐12p40 and IFN‐ γ . Next, we applied the drug topically twice daily in a 0.5% hydrogel formulation. While the local PASI did not change, topical DLX105 mediated significant reductions of mRNA levels of key proinflammatory cytokines when compared to placebo, and this effect was further enhanced after weekly tape stripping of plaques to increase drug penetration. These results suggest that longer treatment periods and/or increased local drug concentrations might result in better therapeutic efficacy of topically applied DLX105. In sum, we can show for the first time that local inhibition of TNF‐ α is sufficient to mediate a biological response in psoriasis that translates into clinical efficacy.